GUI Bloopers : - Johnson, Jeff (Morgan Kaufmann Publishers, 2000)
GUI Bloopers looks at user interface design bloopers from commercial software, Web sites, and information appliances, explaining how intelligent, well-intentioned professionals made these dreadful mistakes--and how you can avoid them. While equipping you with all the theory needed to learn from these examples, GUI expert Jeff Johnson also presents the reality of interface design in an entertaining, anecdotal, and instructive way.